A tangible head model showing semicircular canals for demonstrating the physical treatment for BPPV. (2nd December 2015) - Fujisaka, Michiro; Akaogi, Katsu-Ichi; Shojaku, Hideo
Abstract: Conclusions: It was shown that practicing with a tangible head model with semicircular canals is a useful educational tool for learning the physical treatment for BPPV. Objectives: To assess the efficacy of using a tangible head model with semicircular canals to teach the physical treatment for BPPV. Methods: This study compared the number of canalith particles in the posterior semicircular canal that 20 participants could move from the ampulla to the utricle, before and after practicing with the tangible model. Results: Before practicing with the model, they could move 2.5 (mean value) of 10 canalith particles. However, after practicing, they could move 6.6 (mean value) of 10 canalith particles. There was a statistical difference ( p < 0.01) between the two trials.